Premarital counseling: the professional's handbook - Stahmann, Robert; Hiebert, William (Toronto: Lexington Books, 1987)
Contents: Foundations of premarital counseling. Conjoint couple premarital. Counseling. Group premarital counseling. Marrying again. Special topics in primarital counseling. Fundaciones de aconsejar premarital. Aconsejando. Grupo el aconsejos premarital. Casándose de nuevo. Temas especiales de consejos primarital
Includes references and index
Keywords: Aconsejando matrimonios - matrimonios